2018
DOI: 10.3390/su10030698
|View full text |Cite
|
Sign up to set email alerts
|

The Outcomes of Corporate Social Responsibility to Employees: Empirical Evidence from a Developing Country

Abstract: Abstract:Employees creativity has been recognized as a crucial part of an organization's ability to be innovative. To know which factors contribute to employee involvement in creative work, in this paper, we first examine the effects of corporate social responsibility (CSR) to employees. Moreover, we study the employees' positive work attitudes and their intention to leave as a mediating mechanism to explain the effect of CSR to employees on the involvement of employees in creative work. Survey data from 209 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 112 publications
3
48
0
Order By: Relevance
“…Previous studies have confirmed that gender differences [44], age [45], education level [46,77], income [47,78], and work experience [9,73] all contribute to green purchasing behavior. Hence, these demographic factors were included as control variables in the present study.…”
Section: Control Variablesmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies have confirmed that gender differences [44], age [45], education level [46,77], income [47,78], and work experience [9,73] all contribute to green purchasing behavior. Hence, these demographic factors were included as control variables in the present study.…”
Section: Control Variablesmentioning
confidence: 93%
“…Although English is the most widely used foreign language in both Peru and Bangladesh, an English version of the present study was translated into the local languages (Spanish and Bengali, respectively) in order to enhance the accuracy of the responses. Following the approach of similar studies [9,27,73], we have used a translation and back translation method, which is common in cross-cultural research [74]. First, one local language expert in each country translated the original survey items into the relevant local language.…”
Section: Instrument Pre-testingmentioning
confidence: 99%
“…However, most research in this field focuses on developed countries. Existing literature has called for CSR-related studies in developing countries [7][8][9]. Our study fills this gap by conducting a study about firms' CSR in China, which is the second-largest economic entity in the world.…”
Section: Introductionmentioning
confidence: 99%
“…More than half the respondents had over 10 years' professional experience 60% (105); 22.86% (40) had 1-5 years' experience; 13.71% (24) had 6-10 years' experience; 3.43% (6) had less than a year of professional experience. The following positions were represented: directors 5.14% (9); managers 18.29% (32); specialists 67.43% (118); experts 3.43% (6); analysts 1.71% (3); assistants 0.57% (1); others 3.43% (6). Among respondents, 67.43% (118) had a master's degree; 17.71% (31) had a bachelor's degree; 11.43% (20) had an engineer's degree; 1.14% (2) had a high-school diploma; 2.29% (4) of questionnaires were left blank.…”
Section: Samplingmentioning
confidence: 99%
“…70% perceive sustainability as a key element in their management programs [3]. Organizations which include in their strategies practices and activities that are in line with the idea of sustainability are called sustainable enterprises [1,[4][5][6]. What distinguishes a sustainable enterprise is, among others, the fact that its dominating capital is social capital that is based on good relationships between itself and its external and internal environments, including its employees.…”
Section: Introductionmentioning
confidence: 99%